UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAN FRAKSI - FRAKSI AKAR SALUANG BALUM (Lavanga sarmentosa (Blume) Kurz) - Dwiannur, Febriandi Ramadhan; Irawan, Yogie; Billi, Joseph; Makani, Mawaqit (STIKES Borneo Cendekia Medika, 2024)
Reactive oxygen species (ROS) occur due to the integration between production and excretion of antioxidants in the body, and the accumulation of ROS in tissues can cause oxidative stress. Free radicals are known to be dangerous and threaten human health. Compounds that can inhibit the activity of free radicals are antioxidants. Saluang balum roots (Lavanga sarmentosa (Blume) Kurz) are traditional medicines that have the potential as antioxidants with flavonoid, steroid and tannin compounds. The purpose of this study was to determine the antioxidant activity of saluang balum roots. Testing of antioxidant activity against ethanol extract and saluang balum root fractions was carried out using the DPPH (2,2-diphenyl-1-picrylhidrazyl) method. The results showed that the group of extracts and fractions of saluang balum roots had antioxidant activity. The ethyl acetate fraction had good antioxidant activity with an active category having an IC50 value of 84.24 (IC50 value, 50-100).